Evaluation of HOXC8 in crested Swiss chicken. (18th May 2018) - Joller, S.; Ammann, P.; Flury, C.; Drögemüller, C.
Summary: The crest in chicken consists of elongated and upraised feathers, as seen in various breeds such as the Silkie chicken. Recently, the still unknown causative mutation for the crest phenotype was assigned to chromosome 33 and an ectopic expression of HOXC8 was shown. The aim this study was to evaluate whether the crest phenotype in a local Swiss chicken breed, the Appenzeller Spitzhaubenhuhn, is associated with HOXC8 . Three previously reported crest‐associated flanking markers at the HOXC8 locus were genotyped in cohorts of this breed and two other local breeds without the crest phenotype. For the Appenzeller Spitzhaubenhuhn chicken showing the crest phenotype, no clear association of the reported markers could be revealed. Furthermore, the two exons of HOXC8 were sequenced in crested chicken of the Appenzeller Spitzhaubenhuhn and Silkie breeds and revealed no evidence of polymorphisms within the coding region of HOXC8 . Therefore, the molecular genetic etiology for the crest phenotype in the investigated breeds remains unclear.